Agile Software Development with HP Agile Manager - Tal, Liran; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2015)
Agile development practices have been widely adopted in a variety of organizations, yet only a few tools are available to help make the practical process of managing agile teams less painful and more successful. HP Agile Manager is a purpose-built SaaS-based Agile planning tool. HP Agile Manager provides a simpler, smarter way to manage collaborative development. Liran Tal provides a practical, concise approach to using Agile Manager in a variety of settings to better plan, conduct, and manage software releases within development teams. His step-by-step approach will show you how to plan your product$1 (Bs features, streamline the agile sprint process, work with user stories, and track defects throughout the development process. Agile Manager can work for small startups, mid-sized teams, as well as scale up for bigger organizations as a cost-effective and flexible tool to apply agile techniques to improve your software development process.s
Keywords: Computer science; Computer Science; Computer Science, general; Electronic books